Project-Based Learning Model with Blended Learning in Academic Writing: A Need Analysis - Ilham, Ilham; Irwandi, Irwandi; Ayun, Zakiyah Qurata; Wida, Saniyatil (JOLLT Journal of Languages and Language Teaching, 2025)
Conducting a need analysis is crucial for tailoring academic writing instruction to meet the students’ need. Need analysis serve as systematic tool for developing relevant learning materials that align with students’ learning needs. This research hold significant importance in adressing the integration of project-based learning (PjBL) and blended learning within the context of academic writing. By identifying the needs of students, it provides valuable insight for culliculum designers and educators in English education program. The research aims to identify the students' need for project-based learning with blended learning in academic writing. This study is conducted as survey research at the English education study program at Muhammadiyah University of Mataram and Mandalika University of Education. The questionnaire of collecting data consists of 61 statements with 11 factors. The result of the research shows that all of the students need eleven factors such as learning objectives, topic needs, teaching material requirements, needs assessment, the need of PJBL syntax, blended learning, social system need, requirement principle of reaction, need of support system, learning impact need, and need for impact accompanying learning. The results of this research are expected contributing to the lecturers, stakeholders, and curriculum development of project-based blended learning in academic writiting at the English Education department.